It's not what you say, it's how you say it: A retrospective study of the impact of prosody on own-name P300 in comatose patients. (March 2022) - Pruvost-Robieux, Estelle; André-Obadia, Nathalie; Marchi, Angela; Sharshar, Tarek; Liuni, Marco; Gavaret, Martine; Aucouturier, Jean-Julien
Highlights: Acoustic properties of own-name stimuli used in clinical practice are very variable. Prosody of own-name stimuli influences latencies of the P300 response when obtained. No evidence that the prosody of own-name stimuli influences P300 occurrence. Abstract: Objective: The acoustic characteristics of stimuli influence the characteristics of the corresponding evoked potentials in healthy subjects. Own-name stimuli are used in clinical practice to assess the level of consciousness in intensive care units. The influence of the acoustic variability of these stimuli has never been evaluated. Here, we explored the influence of this variability on the characteristics of the subject's own name (SON) P300. Methods: We retrospectively analyzed 251 disorders of consciousness patients from Lyon and Paris Hospitals who underwent an "own-name protocol". A reverse correlation analysis was performed to test for an association between acoustic properties of own-names stimuli used and the characteristics of the P300 wave observed. Results: Own-names pronounced with increasing pitch prosody showed P300 responses 66 ms earlier than own-names that had a decreasing prosody [IC95% = 6.36; 125.9 ms]. Conclusions: Speech prosody of the stimuli in the "own name protocol" is associated with latencies differences of the P300 response among patients for whom these responses were observed. Further investigations are needed to confirm these results. Significance: Speech prosody of the stimuli in the "own name protocol" is a non-negligible parameter, associated with P300 latency differences. Speech prosody should be standardized in SON P300 studies.